Analisis Theory of Planned Behavior Terhadap Niat Berwirausaha Mahasiswa Universitas Widya Dharma Klaten - Rizky Windar Amelia; Syska Lady Sulistyowatie (Jurnal Akuntansi, 2022)
This study aims to examine the variables in the theory of planned behavior on the entrepreneurial intention of Widya Dharma University students, Klaten. These variables include behavioral attitudes, subjective norms, and perceptions of behavioral control. The independent and dependent variables used in this research adopted the model of Mwiya et al. (2017). With a total of 90 respondents coming from students who have taken Entrepreneurship courses at Widya Dharma University Klaten as the sample of this study. Based on the results of data analysis using Multiple Regression with SPSS 20.0, it shows that subjective norm variables and perceived behavioral control can influence students' entrepreneurial intentions. Keywords: Behavioral Attitudes, Subjective Norms, Perceived Behavioral Control, and Entrepreneurial Intention